Exploring the Role and Mechanism of pAMPKα-Mediated Dysregulation of Brf1 and RNA Pol III Genes. (21st April 2021) - Wu, Teng; Zhang, Dongkun; Lin, Mingen; Yu, Lihong; Dai, Ting; Li, Shuai; Yu, Fenghai; Lu, Lei; Zheng, Liling; Zhong, Shuping
Abstract : TF IIB-related factor 1 (Brf1) is a key transcription factor of RNA polymerase III (Pol III) genes. Our early studies have demonstrated that Brf1 and Pol III genes are epigenetically modulated by histone H3 phosphorylation. Here, we have further investigated the relationship of the abnormal expression of Brf1 with a high level of phosphorylated AMPK α (pAMPK α ) and explored the role and molecular mechanism of pAMPK α -mediated dysregulation of Brf1 and Pol III genes in lung cancer. Brf1 is significantly overexpressed in lung cancer cases. The cases with high Brf1 expression display short overall survival times. Elevation of Brf1 expression is accompanied by a high level of pAMPK α . Brf1 and pAMPK α colocalize in nuclei. Further analysis indicates that the carcinogen MNNG induces pAMPK α to upregulate Brf1 expression, resulting in the enhancement of Pol III transcription. In contrast, inhibiting pAMPK α decreases cellular levels of Brf1, resulting in the reduction of Pol III gene transcription to attenuate the rates of cell proliferation and colony formation of lung cancer cells. These outcomes demonstrate that high Brf1 expression reveals a worse prognosis in lung cancer patients. pAMPK α -mediated dysregulation of Brf1 and Pol III genes plays important roles in cell proliferation, colony formation, and tumor development of lung cancer. Brf1 may be a biomarker for establishing the prognosis of lung cancer. It is a new mechanism that pAMPK α mediates dysregulation of Brf1 and Pol III genes to promote lung cancer development.